2020
DOI: 10.1038/s41598-020-68431-2
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of flowering time gene FT is associated with halving of time to flowering in coconut

Abstract: Coconut palm has two distinct types-"tall" and "dwarf"-which differ morphologically. Tall coconut varieties need 8-10 years to start flowering, while dwarf coconut varieties only require 3-5 years. We compared seedling and reproductive stage transcriptomes for both coconut types to determine potential molecular mechanisms underlying control of flowering time in coconut. Several key genes in the photoperiod pathway were differentially expressed between seedling and reproductive leaf samples in both tall and dwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…In Brachypodium , alternative splicing of FT2 generates two splice variants, FT2α and FT2β , and the latter cannot interact with FD but can form heterodimers with the former and FT1 to prevent floral initiation 53 . In coconut, a shorter alternative splice variant of FT was extensively present in the dwarf varieties, which need fewer years to begin blooming than the tall varieties in which no shorter variant of FT has been found 54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brachypodium , alternative splicing of FT2 generates two splice variants, FT2α and FT2β , and the latter cannot interact with FD but can form heterodimers with the former and FT1 to prevent floral initiation 53 . In coconut, a shorter alternative splice variant of FT was extensively present in the dwarf varieties, which need fewer years to begin blooming than the tall varieties in which no shorter variant of FT has been found 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Cases of alternative splicing of FT have been reported in Brachypodium 53 and coconut 54 . In Brachypodium , alternative splicing of FT2 generates two splice variants, FT2α and FT2β , and the latter cannot interact with FD but can form heterodimers with the former and FT1 to prevent floral initiation 53 .…”
Section: Discussionmentioning
confidence: 99%
“…AP1 accumulation in the meristem is necessary for flowering induction 52 confirmed by earlier results, which indicated that FT can act as a redundancy gene of LFY to activate AP1 53 . A recent transcriptomic study failed to detect an upregulation of LFY in an early flowering coconut genotype 54 . However, it is possible that the signaling cascade may differ from the classical Arabidopsis flowering induction.…”
Section: Discussionmentioning
confidence: 94%
“…Apart from unique variants and SVs identified in the flowering genes such as Hd3a, RFT1, OsMADS14, OsMADS15, and OsMADS56 (Tables S8 and S9), there were changes in the splicing events (Tables 2 and S7), which could have contributed to the differential expression pattern between PSRR-1 and Cypress. Differential AS events in rice were reported as coping mechanisms under adverse environments [41][42][43], and specifically, the flowering time in coconut was influenced by AS of the FT gene [44].…”
Section: Discussionmentioning
confidence: 99%